2020
DOI: 10.1101/2020.05.29.123752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigations of dimethylglycine (DMG), glycine betaine and ectoine uptake by a BCCT family transporter with broad substrate specificity inVibriospecies

Abstract: Fluctuations in osmolarity are one of the most prevalent stresses to which bacteria must adapt, both hypo- and hyper-osmotic conditions. Most bacteria cope with high osmolarity by accumulating compatible solutes (osmolytes) in the cytoplasm to maintain the turgor pressure of the cell. Vibrio parahaemolyticus, a halophile, utilizes at least six compatible solute transporters for the uptake of osmolytes: two ABC family ProU transporters and four betaine-carnitine-choline transporter (BCCT) family transporters. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 88 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The V. parahaemolyticus ectB deletion mutant that cannot grow in high NaCl growth conditions in the absence of exogenous osmolytes, as was previously shown was used as a positive control (34,36). We examined growth of wild type and the ectB mutant in M9 minimal media supplemented with glucose and 6% NaCl (M9G 6%NaCl), in the presence and absence of DMSP.…”
Section: Vibrio Parahaemolyticus Can Utilize Dimethylsulfoniopropionamentioning
confidence: 99%
See 3 more Smart Citations
“…The V. parahaemolyticus ectB deletion mutant that cannot grow in high NaCl growth conditions in the absence of exogenous osmolytes, as was previously shown was used as a positive control (34,36). We examined growth of wild type and the ectB mutant in M9 minimal media supplemented with glucose and 6% NaCl (M9G 6%NaCl), in the presence and absence of DMSP.…”
Section: Vibrio Parahaemolyticus Can Utilize Dimethylsulfoniopropionamentioning
confidence: 99%
“…We examined growth of wild type and the ectB mutant in M9 minimal media supplemented with glucose and 6% NaCl (M9G 6%NaCl), in the presence and absence of DMSP. Growth pattern analysis after 24 h showed that the lag phase of the wild-type strain without exogenous compatible solutes is approximately six hours with a growth rate of 0.042 h -1 , while the ΔectB mutant did not grow (36) (Fig. 1).…”
Section: Vibrio Parahaemolyticus Can Utilize Dimethylsulfoniopropionamentioning
confidence: 99%
See 2 more Smart Citations